Intergenerational mobility of young Europeans: a comparative analysis of social and political consequences - Schuck, Bettina (2019)
This thesis sets out to investigate social and political consequences of young Europeans’ experiences of intergenerational mobility, i.e., achieving a higher or lower socioeconomic status than one’s parents. In particular, it aims at providing a better understanding of how young Europeans’ (aged 35 and younger) experience of intergenerational mobility shapes their well-being and normative support for the welfare state. Apart from a descriptive overview on the status quo of intergenerational mobility among young Europeans in three dimensions (educational mobility, economic mobility, and expectations of future mobility), the main objective of the empirical analyses is to investigate the extent to which the psychological experience of intergenerational mobility, independent from the direct impact of one’s own and parental socioeconomic status, affect different dimensions of well-being and political attitudes. To this end, I apply diagonal reference models, the only method suitable to disentangle the effects of mobility, social origin, and social destination. With respect to possible consequences of intergenerational mobility for the young people’s well-being, I investigate several hypotheses about individual and societal differences between mobile and non-mobile individuals. In line with the theoretical prediction that psychological mobility effects are more likely to occur in status-based societies, I find net mobility effects in Continental Europe and the Anglo-Saxon countries. Yet, contrary to the theoretical expectations, I also find net mobility effects in the Nordic countries. In terms of political consequences of intergenerational mobility of young Europeans, I test two competing sets of hypotheses about differences in normative welfare state attitudes between mobile and non-mobile individuals. Thereby, the first set relies on material self-interest as the main determinant for welfare state support, while the second set is based on factors beyond material self-interest, such as deservingness perceptions. The empirical findings do not support the prediction of mobile individuals being more sympathetic with benefit recipients. This arguably owes to the fact that the well-known determinant material self-interest apparently plays a similar role in determining normative welfare state attitudes for the mobile as for the non-mobile.
Keywords: Hochschulschrift